2018
DOI: 10.3382/ps/pex289
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the addition of organic acids in the feed and/or water for broilers and the subsequent recovery of Salmonella Typhimurium from litter and ceca

Abstract: Three separate broiler Salmonella Typhimurium challenge experiments were conducted evaluating efficacy of formic and propionic acid feed supplements to suppress environmental and cecal Salmonella Typhimurium prevalence. In experiment 1, broilers were provided feed with 1 kg/ton formic acid or 5 kg/ton propionic acid feed additives or a basal control diet. At the day of placement, half of the pens were inoculated with seeder chicks orally challenged with a marker strain of Salmonella Typhimurium and to yield ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 22 publications
1
20
0
2
Order By: Relevance
“…Formic acid, a kind of SCFA, is produced by intestinal bacteria fermenting undigested starch or fiber polysaccharides that are unused to the host. SCFAs have important physiological significance to the host ( Meimandipour et al, 2010 ; Rinttila and Apajalahti, 2013 ), of which formic acid could improve the intestinal morphology of broilers ( Garcia et al, 2007 ) and inhibit the growth of pathogens ( Bourassa et al, 2018 ). The results of the present study showed that B. licheniformis or enramycin can maintain the intestinal health by increasing the content of cecal formic acid in SNE-infected broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Formic acid, a kind of SCFA, is produced by intestinal bacteria fermenting undigested starch or fiber polysaccharides that are unused to the host. SCFAs have important physiological significance to the host ( Meimandipour et al, 2010 ; Rinttila and Apajalahti, 2013 ), of which formic acid could improve the intestinal morphology of broilers ( Garcia et al, 2007 ) and inhibit the growth of pathogens ( Bourassa et al, 2018 ). The results of the present study showed that B. licheniformis or enramycin can maintain the intestinal health by increasing the content of cecal formic acid in SNE-infected broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of Salmonella Pullorum was not directly confirmed, which may be the major limitation of the current study. There was another possibility that the chicks were still exposed to environmental Salmonella challenge during the grower phase (Bourassa et al, 2018) although did not show any clinical signs. Supplementation of OA in the combination of feed and water could alleviate the adverse effects of S .…”
Section: Discussionmentioning
confidence: 99%
“…Organic acids (OA), which primarily composed of short-chain fatty acids (SCFAs, ≤C6) and medium-chain fatty acids, are both bacteriostatic and bactericidal, and thus show promise as antibiotic alternatives in reducing colonization by pathogens. A series of studies have tested the efficacy of OA on reducing colonization with Salmonella in broiler chickens, turkeys, and pigs in an agricultural setting, and controlling Salmonella in meat and poultry products post-slaughter (Mani-Lopez et al, 2012; Arguello et al, 2013; Evans et al, 2017; Bourassa et al, 2018). The primary mechanisms of OA for reducing pathogenic bacteria include cytoplasmic acidification with subsequent uncoupling of energy production and regulation, and the accumulation of the dissociated acid anion to toxic levels in vitro (Mani-Lopez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Whether this is true of formic acid remains to be determined. However, more recently, Bourassa et al (132) did note that feeding formic acid at 4 g per ton for a 6 week grow-out period in broiler chicks reduced cecal S. Typhimurium concentrations below detection levels.…”
Section: Impact On Foodborne Pathogens In the Gastrointestinal Tractmentioning
confidence: 99%
“…However, acids in the feed have the opportunity as they enter into the GIT to continue to exhibit antimicrobial activities. Externally introduced acid antimicrobial activity in the GIT is potentially dependent on numerous factors including GIT acid concentration, GIT site of activity, level of GIT pH and oxygen, age of the animal, and the corresponding composition of microbial populations inhabiting the GIT as a function of GIT location and animal maturity ( 21 , 24 , 128 132 ). In addition, the resident GIT anaerobic microbial population, which becomes more dominant in the lower GIT sections of the monogastric animal as it matures, is actively producing organic acids via fermentation, which, in turn, are also potentially antagonistic to transient pathogens entering the GIT ( 17 , 19 21 ).…”
Section: Impact On Foodborne Pathogens In the Gastrointestinal Tractmentioning
confidence: 99%